Fluid-fluid interactions in a system of CO2, oil, surfactant solution, and brine at high pressures and temperatures - A Malaysian reservoir case - Talebian, S.H. (Elsevier, 2014)
In this study, the interactions of fluids involved in foam assisted CO2 enhanced oil recovery process are studied at the prevailing conditions of a shallow Malaysian (sandstone) oil reservoir (pressure of 70-200bar, and temperature of 102Â°C). The equilibrium CO2 solubility into the reservoir brine, and crude oil, and the effect of foaming agent surfactants on the CO2 solubility into the aqueous phase are measured by using an equilibrium high pressure cell. The interfacial tension (IFT) measurements of gas-liquid and liquid-liquid systems are accomplished by utilizing the axisymmetric drop shape analysis (ADSA) adapted in a pendant drop tensiometer. Two in-house developed surfactants (FomaxII and FomaxVII) are compared with the industrial bench-mark surfactant, alpha olefin sulfonate (AOS), for the structure-property analysis. FomaxVII is a blend of anionic and amphoteric surfactants, with a short-branched chain structure which contains CO2-philic groups. FomaxII is a blend of anionic surfactants, with long, straight-tail hydrocarbon structure.The results show that the dissolution of CO2 into the aqueous phase increased significantly in the presence of 1wt surfactants at the reservoir prevailing conditions. A relationship was also observed between the surfactant molecular structure and its effect on the CO2/aqueous phase interface. The results of this study are useful to evaluate the mechanisms of immiscible CO2 flooding as well as to design the foam assisted CO2-EOR applications for the case Malaysian or similar oil reservoir. Â© 2014 Elsevier B.V.